THE EFFECT OF SERVICE QUALITY AND HOSPITAL FACILITIES ON PATIENT LOYALTY WITH PATIENT SATISFACTION AS A MEDIATION VARIABLE (STUDY AT PKU MUHAMMADIYAH HOSPITAL BLORA) - Mazirul Agung Santara; Wani Devita Gunardi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The purpose of this research is to analyze the effect of service quality and facilities on customer loyalty through patient satisfaction as a mediating variable. The population used in this study were inpatients of PKU Muhammadiyah Blora Hospital. Where the sample was 256 respondents, with a research instrument in the form of a questionnaire. Data analysis using SPSS. The results of this study indicate that the quality of service and facilities has a direct effect on patient satisfaction. And patient satisfaction is able to mediate the indirect relationship between service quality and facilities to customer loyalty. To increase patient loyalty, PKU Muhammadiyah Blora Hospital needs to provide effective communication training for doctors, nurses, and support staff so that they can serve patients with empathy and professionalism. Improve the comfort of the waiting room, inpatient room, and other supporting facilities (such as free Wi-Fi, children's playroom, or lactation room). Develop hospital applications to facilitate access to information such as doctor's schedules, online registration, or control schedule reminders.